Educational systems of Uzbekistan and Singapore: historical and contemporary contexts - Mamatova, Nazgul (MMIT Proceedings, 2025)
The article analyses the education quality management models in Uzbekistan and Singapore, identifying key differences and similarities in institutional structure, assessment and monitoring systems, teacher training and community engagement. It examines reform processes in Uzbekistan and successful practices in Singapore, including digitalisation of education and international rankings. The author highlights the importance of integrating innovative methods and professional development to improve the quality of education in both countries. Keywords: Uzbekistan, Singapore, quality of education, educational reform, teacher training, digitalization, international rankings.